2007
DOI: 10.1007/s10646-007-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium tolerance and accumulation by two species of Iris

Abstract: Seedlings of Iris lactea var. chinensis (Fisch.) Koidz. and I. tectorum Maxim. were subjected to 0-160 mg l(-1) Cd in hydroponic system and harvested after 42 days to determine effects on root and shoot dry mass. A subset of 16-day-old seedlings was exposed to 1000 mg l(-1) Cd to characterize sub-cellular localization of Cd in root cells. The Cd contents in the shoots of I. lactea var. chinensis reached 529 microg g(-1 )dry weight (dw) at 80 mg l(-1) Cd treatment and in the shoots of I. tectorum reached 232 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 26 publications
4
45
1
2
Order By: Relevance
“…1), NY2 and NY5 growing in Cd-contaminated soil might employ the accumulation mechanism. This suggested that H. tuberosus genotypes NY2 and NY5 efficiently translocated Cd from roots to shoot and leaves, showing a Cd-phytoextraction potential, as in some other plant species [38,39]. Biomass production by NY2 and NY5 was not sharply decreased with an increase in Cd supply (in NY5 there was even an increase in biomass at 2.5 and Different letters within a column indicate the significant differences among the treatments ( p 0.05, n ¼ 6).…”
Section: Discussionmentioning
confidence: 87%
“…1), NY2 and NY5 growing in Cd-contaminated soil might employ the accumulation mechanism. This suggested that H. tuberosus genotypes NY2 and NY5 efficiently translocated Cd from roots to shoot and leaves, showing a Cd-phytoextraction potential, as in some other plant species [38,39]. Biomass production by NY2 and NY5 was not sharply decreased with an increase in Cd supply (in NY5 there was even an increase in biomass at 2.5 and Different letters within a column indicate the significant differences among the treatments ( p 0.05, n ¼ 6).…”
Section: Discussionmentioning
confidence: 87%
“…Root elongation can be reduced by either the inhibition of root cell division and/or the decrease of cell expansion in the elongation zone (Fiskesjo 1997). Since inhibition of root elongation appears to be the first visible effect of metal toxicity, the root length can be used as an important tolerance index (Piechalak et al 2002;Belimov et al 2003;Odjegba and Fasidi 2004;Han et al 2007).…”
Section: Rootmentioning
confidence: 99%
“…It has been reported that some species of the Iris genus, such as I. pseudacorus, I. tectorum and I. lacteal, are capable of accumulating high levels of Cd, as well as other toxic metals, in their shoots from the soil or hydroponic solution (Caldelas et al 2012;Han et al 2007). However, to our knowledge, the mechanisms of metal tolerance and accumulation in Iris genus plants are poorly understood.…”
mentioning
confidence: 99%